Карпатська Україна як етап українського державотворення - Віднянський, С. (Український історичний журнал, 2019)
Здобуття автономії Підкарпатської Русі (Закарпаття) у складі Чехословаччи-
ни у жовтні 1938 р. і проголошення незалежності Карпатської України в берез-
ні 1939 р. ввійшло в історію як відчайдушна спроба українців напередодні Другої
світової війни відновити національну державність на окремо взятій етнічній
території як зародок майбутньої соборної України. Ці події стали другим у
минулому столітті, після Української національної революції 1917–1921 рр.,
етапом у боротьбі українців за створення національної держави. Водночас цей
феномен української історії викликав чимало фальсифікацій і необґрунтованої
критики як свого часу з боку радянських істориків, так і зарубіжних та деяких
сучасних закарпатських авторів із метою дискредитації перебігу й значення
державотворчих процесів на Закарпатті наприкінці 1930-х рр. і все ще залишає
чимало дискусійних питань для дослідників. Із нагоди 80-річного ювілею прого-
лошення незалежності Карпатської України й з урахуванням сучасних реалій
особливо важливим видається звернення до уроків державотворення, зокрема
нове бачення (прочитання) історичних подій, які відбувалися на Закарпатті
напередодні Другої світової війни. На основі аналізу значного історіографічного
доробку та використання документальних джерел із проблеми у статті ви-
світлюються, поряд із вузловими й дискусійними питаннями власне історії
Карпатської України, історичні події, що передували проголошенню її незалеж-
ності, а саме характер і генеза суспільно-політичних та особливо національно-
культурних процесів на Закарпатті, передусім динамічні, складні події у краї
та навколо нього після завершення Першої світової війни і часів його входження
до складу Чехословаччини в 1919–1939 рр., які підготували ґрунт для здобуття
автономії і проголошення незалежності Карпатської України. Наголошується
також на історичному значенні розбудови карпатоукраїнської державності,
зокрема її впливі на актуалізацію загальноукраїнських проблем у міжнародних
відносинах і розвиток національно-визвольного руху українського народу за суве-
ренну, незалежну, соборну національну державу. Obtaining autonomy of Subcarpathian Rus (Zakarpattia) as part of the Czechoslovak
Republic in October 1938 and declaring the independence of Carpathian Ukraine
in March 1939 went down in history as a desperate Ukrainians’ attempt to recreate
national power in a single ethnic territory on the eve of World War II as the beginning
of future united Ukraine. These events became the second stage in the Ukrainian
struggle for the creation of a national state in the last century, after the
Ukrainian revolution of 1917–1921. At the same time, this phenomenon of Ukrainian
history caused a lot of falsifications to discredit the significance of state-building
processes in Zakarpattia in the late 1930s and still leaves many controversial issues
for researchers. Based on an analysis of the significant historiographic heritage and
the use of documentary sources on the problem, the article is devoted to the 80th
anniversary of the independence of Carpathian Ukraine. It highlights, along with
key issues and debates about the history of Carpathian Ukraine, the historical events
preceding its independence, in particular, the nature and the genesis of sociopolitical
and especially national cultural processes in Zakarpattia. First of all, the article
demonstrates the dynamic and complex events in the region after the World War I and
during its development in the Czechoslovak Republic in 1919–1939s, which paved
the way for the autonomy and independence of Carpathian Ukraine. The author focuses on the historical significance of building Carpatho-Ukrainian statehood, in particular on its influence on the actualization of all-Ukrainian problems in
international relations and on the development of national-liberation movement of
Ukrainians for a sovereign, independent, integral Nation-State. Despite the short
period of Carpatho-Ukraine’s history, it has been in the focus of attention of the
public opinion on other Ukrainian lands, of Ukrainian diaspora and many European
States. A short history of the existence of Carpatho-Ukrainian State was caused by
the failure to find a solution to the Ukrainian issue in international relations in the 1930s.